Proceedings of the 2015 ACM SIGCHI Conference on Creativity and Cognition 2015
DOI: 10.1145/2757226.2757246
|View full text |Cite
|
Sign up to set email alerts
|

Biological Citizen Publics

Abstract: Low-cost genetic sequencing, coupled with novel social media platforms and visualization techniques, present a new frontier for scientific participation, whereby people can learn, share, and act on data embedded within their own bodies. Our study of 23andMe, a popular genetic testing service, reveals how users make sense of and contextualize their genetic results, critique and evaluate the underlying research, and reflect on the broader implications of genetic testing. We frame user groups as citizen science p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 22 publications
(27 reference statements)
0
15
0
Order By: Relevance
“…Country of study, study method, and the number of papers addressing each review question are presented in Table 1. Twenty‐five studies used quantitative methods, 18–42 seven qualitative methods, 43–49 and three mixed methods 50–52 . There were eight case studies, 53–60 reporting on 12 individual cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Country of study, study method, and the number of papers addressing each review question are presented in Table 1. Twenty‐five studies used quantitative methods, 18–42 seven qualitative methods, 43–49 and three mixed methods 50–52 . There were eight case studies, 53–60 reporting on 12 individual cases.…”
Section: Resultsmentioning
confidence: 99%
“…There were eight case studies, 53–60 reporting on 12 individual cases. The majority of studies (72.1%) were conducted in the United States, 18,20–33,35–38,40–42,46–48,50,52,55,56,58,60 others were from Australia (11.6%), 34,39,49,51,57 Europe (4.7%), 44,45 and a single paper each from Canada, 59 France, 54 Italy, 19 Spain 53 and the United Kingdom 43 . Eighteen papers presented data from one of three larger studies: Impact of Personal Genomics (PGen) used longitudinal surveys with a cohort of 1648 consumers who had purchased 23andme (SNP array) or Pathway Genomics (undisclosed product); Scripps Genomic Health Initiative (SGHI) studied 2037 consumers who purchased “Health Compass”, a subsidised DTC‐GT produced by Navigenics, which provided genetic risk information for common diseases and offered in‐house genetic counselling; and Genomics: National Insights of Australians (Genioz) explored the views and experiences of the Australian public regarding DTC‐GT and includes surveys and consumer interviews.…”
Section: Resultsmentioning
confidence: 99%
“…However, to date, HCI research on interaction with personal genomic data is in its infancy. Studies that investigated the information practices of personal genomic data users found that nonexperts seek to contextualize and compare their personal data with others (eg, family members and others with similar medical conditions) [2,3]. The family-relevant nature of genetic data highlights the need for tools to enable nonexperts to explore not only their own data but also to compare and contrast it with the data of others.…”
Section: Introductionmentioning
confidence: 99%
“…Such comparisons enable users to explore what variants they share with others and what sets them apart, thus increasing the understanding of their genetic makeup and enriching the genomic narrative people can construct. There has been a growing interest in exploring how people form social ties around health conditions caused or influenced by genetic characteristics—what Kuznetsov et al have called biosociality [2]. In this paper, we discuss findings from 2 user studies focusing on assessing the usability and understandability of comparing genetic reports of family members using alternative prototypes of CrossGenomics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation